Intra- and Interobserver Study Investigating the Adapted EFSUMB Bosniak Cyst Categorization Proposed for Contrast-Enhanced Ultrasound (CEUS) in 2020 - Münch, Frederic; Silivasan, Emanuel Ioan Eugen; Spiesecke, Paul; Göhler, Friedemann; Galbavy, Zaza; Eckardt, Kai-Uwe; Hamm, Bernd; Fischer, Thomas; Lerchbaumer, Markus Herbert (Ultraschall in der Medizin - European Journal of Ultrasound, 2023)
Background To investigate the inter- and intraobserver variability in comparison to an expert gold standard of the new and modified renal cyst Bosniak classification proposed for contrast-enhanced ultrasound findings (CEUS) by the European Federation of Societies for Ultrasound in Medicine and Biology (EFSUMB) in 2020.Materials and Methods 84 CEUS examinations for the evaluation of renal cysts were evaluated retrospectively by six readers with different levels of ultrasound expertise using the modified Bosniak classification proposed for CEUS. All cases were anonymized, and each case was rated twice in randomized order. The consensus reading of two experts served as the gold standard, to which all other readers were compared. Statistical analysis was performed using Cohen’s weighted kappa tests, where appropriate.Results Intraobserver variability showed substantial to almost perfect agreement (lowest kappa κ=0.74; highest kappa κ=0.94), with expert level observers achieving the best results. Comparison to the gold standard was almost perfect for experts (highest kappa κ=0.95) and lower for beginner and intermediate level readers still achieving mostly substantial agreement (lowest kappa κ=0.59). Confidence of rating was highest for Bosniak classes I and IV and lowest for classes IIF and III.Conclusion Categorization of cystic renal lesions based on the Bosniak classification proposed by the EFSUMB in 2020 showed very good reproducibility. While even less experienced observers achieved mostly substantial agreement, training remains a major factor for better diagnostic performance.
Keywords: CEUS; Bosniak cyst classification; renal cyst; interobserver variability; intraobserver variability